Stress among Flat / Apartment Dwellers (Case Study : Taman Nelly Kolombong) / Zuriati Abd Rahman... [et al.] - Abd Rahman, Zuriati; Jaidi, Asrudi; Sulaiman, Suhaila (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2001)
This project paper is a research about stress problems among people who lives in flat housing or apartments in Nelly Park, Kolombong. It converge upon an area of a police barrack which consist of 347 people. This research is done to find sources that causing stress problems among flat residents. It is because of some factors such as noise, air pollution (unpleasant smell of garbage), and narrow housing space and so on. On this research, some method are used to collect the data either it is from primer data resources nor from the secondary data resources. These methods include interviews, questionnaires, observation and other reference material either by using magazines/ journal, newspapers, encyclopedia, department report or relevant books. The main question in this research is to identify how stress can exist among flat residence. In this research also, the researchers give some suggestions by referring to past research and what the flat residents think.